2015
DOI: 10.4315/0362-028x.jfp-15-081
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Indicator and Pathogenic Microorganisms in Broccoli following Manure Spreading and Irrigation with Fecally Contaminated Water: Field Experiment

Abstract: In 2011 and 2012, trials consisting of experimental plots were carried out to evaluate the presence of pathogenic (Listeria monocytogenes, Salmonella) and prevalence of indicator (Escherichia coli) microorganisms in broccoli fertilized with liquid hog manure or mineral fertilizers and irrigated zero, one, or two times with E. coli-contaminated water. In 2011, results showed that E. coli contamination in broccoli heads was affected by the interval between irrigation and sampling (P = 0.0236), with a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(58 reference statements)
0
5
0
1
Order By: Relevance
“…Certain laboratory experiments have been carried out to determine the efficacy of these waiting times and it was observed that the number of infectious bacteria such as E. coli O157:H7 and Salmonella spp. occurring on farm produce significantly reduced between 1 to 10 days of stoppage of irrigation and soil amendment [145,285,286,291,292,293]. Although some studies stated that some of the pathogens do not really die off but get induced into a dormant form, a state where the pathogens are viable but not culturable (VBNC) under stressful conditions [294], but returns to viable cells when favourable conditions return.…”
Section: Interventions To Prevent Fresh Produce Contamination Priomentioning
confidence: 99%
“…Certain laboratory experiments have been carried out to determine the efficacy of these waiting times and it was observed that the number of infectious bacteria such as E. coli O157:H7 and Salmonella spp. occurring on farm produce significantly reduced between 1 to 10 days of stoppage of irrigation and soil amendment [145,285,286,291,292,293]. Although some studies stated that some of the pathogens do not really die off but get induced into a dormant form, a state where the pathogens are viable but not culturable (VBNC) under stressful conditions [294], but returns to viable cells when favourable conditions return.…”
Section: Interventions To Prevent Fresh Produce Contamination Priomentioning
confidence: 99%
“…There was a greater chance of isolating L. monocytogenes after irrigation than rainfall and this chance was highest within 24 h of the event (Weller et al, 2015b). Other studies have confirmed similarly that irrigation is a risk factor for contamination of pre-harvest foods (Genereux et al, 2015; Weller et al, 2015a). This is often due to the contamination of the water source used for irrigation of the fields (Strawn et al, 2013; Genereux et al, 2015).…”
Section: Entry Of L Monocytogenes Into the Food Chainmentioning
confidence: 53%
“…Other studies have confirmed similarly that irrigation is a risk factor for contamination of pre-harvest foods (Genereux et al, 2015; Weller et al, 2015a). This is often due to the contamination of the water source used for irrigation of the fields (Strawn et al, 2013; Genereux et al, 2015). Along with irrigation, the use of manure as a fertilizer can increase isolation of L. monocytogenes from produce production sites (Watkins and Sleath, 1981; Fenlon et al, 1996; Garrec et al, 2003).…”
Section: Entry Of L Monocytogenes Into the Food Chainmentioning
confidence: 53%
“…As DTA podem ser causadas por diversos agentes como bactérias, fungos, vírus, parasitos, toxinas, prions, agrotóxicos e metais tóxicos. Estão geralmente associadas ao consumo de preparações prontas e vegetais frescos processados ou não GÉNÉREUX et al, 2015). SILVA, 2014).…”
Section: Doenças Transmitidas Por Alimentos (Dta)unclassified